Strategy for Development of Halal Tourism Products and Activities in Indonesia - Wiradharma, Gunawan; Nugroho, Dhimas Setyo; Priyana, Efraim Bavo; Arisanty, Melisa; Batti, Steviani (Business Education Program of Universitas Pendidikan Indonesia, 2024)
As a country with the largest Muslim population globally, Indonesia is one of the world's most important halal tourism markets. Domestic tourism actors must realize this because developing sustainable halal tourism can significantly increase all actors engaged in it. Therefore, this study aims to describe product development strategies and the implementation of halal tourism activities in Indonesia so that Indonesia can become the world's leading halal tourism destination. This study uses a descriptive method to depict the object under study. The study results indicate that Indonesia is a potential and significant tourism market, so a product development strategy and activities for halal tourist attractions are needed so Muslim tourists can better know Indonesia. The strategy has emphasized the development of halal tourism marketing and promotion strategies. Marketing strategy can be done by determining the identity of tourist attractions, identifying the target market, in this case, Muslim tourists, setting prices, and making the differentiation. Meanwhile, the promotion strategy for halal tourism can be done through direct and indirect marketing.